Inovasi Produk dan Digital Marketing dalam mempengaruhi Keputusan Pembelian pada Teras Soreang Kabupaten Bandung - Ema Ambiapuri; Hedi Setiadi; Nur Aini Parwitasari (Universitas Batanghari Jambi, 2023)
This research focuses and aims to test the influence of product innovation and marketing digital on purchasing decisions at UMKM Teras Soreang. The population in the study was a visitor to Teras Soreang Kab Bandung. Samples taken from this study as many as 160 with the methods used namely purposive sampling and snowball sampling. Data were analyzed using SEM methods with Smart PLS 3.0 software. The results of this study show that product innovation has a significant effect on purchasing decisions and digitization has a significant effect on purchasing decisions together and partially. To increase sales, more in-depth training and mentoring is needed to MSMEs Teras Soreang in order to survive in the period after covid 19.